New methodologies for the calculation of Green´s functions for wave problems in two-dimensional unbounded domains - Couto, R. T. (Trends in Computational and Applied Mathematics, 2013)
This work describes the application of new methodologies for the evaluation of the inverse Fourier transforms that yield Green’s functions for both the wave and Helmholtz equations in the entire bidimensional domain.